Using efficiency analysis to measure individual well-being with an illustration for Catalonia - Xavi Ramos (Institute for the Study of Labor (IZA), 2005)
This paper shows how distance functions, a tool typically employed in production economics to measure the distance between a set of inputs and a set of outputs, can be employed to approximate a composite measure encompassing the many dimensions of well-being. It also illustrates how to implement the methodology originally put forth by Lovell et al. (1994), using new data for Catalonia. We draw policy implications and critically appraise the discussed methodology suggesting avenues for further research.
Keywords: D31; D63; I31; I32; 330; well-being; multidimensional poverty; distance function; Catalonia; Armut; Vermögensverteilung; Einkommensverteilung; Lebenszufriedenheit; Messung; Statistische Methode; Katalonien